Strategy of elimination of antibiotcoresistance to carbapenems – actual modern problem - V. V. Vashchuk; T. P. Kyryk; M. I. Kushnirchuk; R. P. Baidala; M. J. Krat; T. V. Khomchenko (Клінічна хірургія, 2022)
Strategy of elimination of antibiotcoresistance to carbapenems – actual modern problem